MANAJEMEN REDAKSIONAL DAN EKSISTENSI MAJALAH (Studi Kasus Praktek Kerja Sehari-hari Redaksi Djaka Lodang Yogyakarta Tahun 2012) - , Eista Swaesti, Dr.Phil. Ana Nadhya Abrar, M.E.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the implementation of Djaka Lodang magazine editorial management in daily work life to maintain its existence as a Java-language magazine. The object of this study is to bring Djaka Lodang magazine as the only Java-language magazine in Yogyakarta. The subject of his research is general director, chief editor, managing editor, editorial crew, and secretary of Djaka Lodang magazine. This research is focus on applied management in the editorial department and its application to maintain the existence of Djaka Lodang magazine. Data were obtained by interview, direct observation, and photo documentation. Data were analyzed with case studies. The results showed that: (1) The editorial of Djaka Lodang magazine is still not look perfect. This represent in the unregular meeting. Djaka Lodang magazine is lack of human resources so that editorial staff is still help the marketing division to promote Djaka Lodang magazine. (2) Djaka Lodang magazine is also not been able to maximize efforts to maintain its existence. Creatif and innovatif human resources is required to manage Djaka Lodang magazine so that Javaness culture and language can be inherently spoken by young generation. While now a days, many young people are lack of Javaness culture and language.